O KATEGORIACH BIBLIJNYCH W POEMACIE KAROLA WOJTYŁY „PIEŚŃ O BLASKU WODY” - Hawryluk, Dorota (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
“The Song of the Brightness of Water”, a piece by Karol Wojtyła created in 1950, is a poetic meditation in complete agreement with the logic of the biblical message. This seems to be demonstrated not only by the directly quoted fragment from the Gospel according to John at the beginning of the poem, which was subjected to in-depth poetic reflection, but also by the original literary transposition of the subject-matter of the biblical categories, which create the ambience of the entire poem. The focus of the interpretation adopted by Karol Wojtyła is on two biblical categories: longing and perception. The analysis of these categories was contrasted with the spiritual process of an individual’s becoming mature enough to enter into a life-giving dialogue with God, which can be observed, for instance, in the song of adoration sung by the protagonist of pain, constituting one of the most-creative extensions of the Gospel’s message by Wojtyła. His focus on the individual’s perception of his/her identity can serve as brilliant evidence of the attempt to reconstruct the concept of the human being present in the poem. In the light of this concept the human is a work of God, created to live in love, and in the likeness and image of God (cf. Gen 1, 27). This fundamental truth is the source of the issue clearly depicted in the poem of the possibility embedded by the Creator in each human being, enabling him/her to participate in the mysteries of God’s Wisdom (cf. Wisdom 6, 1-25) and living life to its fullest. In this context Karol Wojtyła’s poetic description of the main protagonist’s transformation is extremely fascinating. Under the influence of the saving affirmation of the Son of God, the woman from Samaria gains a new identity and discovers a new type of God’s assistance in human life, i.e. His complete involvement in human suffering. Thanks to this, she is able to fully accept the grace given by Christ to enable her to rise above the state of being separated from experiencing love and being released from the consequences of the deep wounding of her soul. The highly original aspect of this vision is that the Samaritan receives the gift of a new self-awareness at the well in Shechem, which from the perspective of the Saviour Himself can symbolise His incessant preservation of the Source of His Filial Identity. In this way the anthropology presented so far, strictly connected with theology, becomes inseparable from Christology, emphasising the Christocentric and Christoformic nature of this poem by Karol Wojtyła.